[Rezension von: Thome, Felix, 1966-, Historia contra Mythos : die Schriftauslegung Diodors von Tarsus und Theodors von Mopsuestia im Widerstreit zu Kaiser Julians und Salustius' allegorischem Mythenverständnis] - Lössl, Josef (The journal of theological studies, 2005)
Following a suggestion of A. Guida, who edited the extant fragments of Theodore of Mopsuestia's response to Julian the Apostate's Contra Galilaeos, Felix Thome embarked on a doctoral project in which he tried to demonstrate that Theodore's anti-allegorical/anti-mythical stance was generally driven by a reaction against the emperor's project to create religion from allegorizing myth, a project not all too different, it may have seemed, from that of many Christian theologians at the time. The thesis that resulted in the present book was supervised by Hermann J. Vogt, who also wrote a foreword for it.